2020
DOI: 10.2196/18102
|View full text |Cite
|
Sign up to set email alerts
|

Development and Implementation of a Web-Based Learning Environment for an Inpatient Internal Medicine Team: Questionnaire Study

Abstract: Background The notion of anytime, anyplace communication is characteristic of the current generation of learners. Such communications have facilitated the growth and integration of a blended or hybrid learning platform in multiple educational settings. However, there are limited reports on the use of an anytime, anyplace communication platform in clinical inpatient medical education. Objective The setting of a high-demand inpatient clinical rotation is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…One study (2.5%) was published in 2022, 20 7 studies (17.5%) were published in 2021, 2,22,23,24,25,26,27 and 8 studies (20.0%) were published in 2020. 28,29,30,3,31,32,33,21 The studies and their corresponding citations are available in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One study (2.5%) was published in 2022, 20 7 studies (17.5%) were published in 2021, 2,22,23,24,25,26,27 and 8 studies (20.0%) were published in 2020. 28,29,30,3,31,32,33,21 The studies and their corresponding citations are available in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The scoping review focused on programs within North America. The majority of included studies (34 studies) were conducted in the United States of America (85.0%) 2,28,34,29,22,30,35,36,37,38,39,40,40,41,42,43,23,31,44,45,24,46, 47,33,25,26,20,21,48,49,50,51,52,53 and 6 studies 54,55,56,57,58,32 were conducted in Canada (15.0%). Two studies had international impact with learners globally using the morning report blog and The Clinical Problem Solvers podcast (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the increased use of digital learning tools in medical education, web tools remain the most frequently utilized digital resource among medical students and residents [ 12 ]. A recent survey study of an inpatient medicine team found that web-based learning interventions improved self-directed learning, communication goals, and learning environment among medical students and residents [ 13 ].…”
Section: Introductionmentioning
confidence: 99%